Preparation method and application of monatomic and precise atom cluster co-loaded catalyst

By using Hmbm to form stable metal molecular clusters with metal centers, the problem of precise regulation of metal clusters on carbon and nitrogen substrates is solved, and the high activity and selectivity of the catalyst is achieved, especially in the field of electrocatalytic nitrate reduction.

CN119877019AActive Publication Date: 2025-04-25HEBEI UNIV OF TECH

Patent Information

Application Number
CN202510061904.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The prior art is difficult to achieve precise regulation of metal clusters on carbon and nitrogen substrates and positioning of active sites, resulting in insufficient catalyst activity and unclear reaction mechanism.

Method used

By using 2-Methyl-1H-benzimidazole-1-methanol (Hmbm) as an organic ligand to form stable metal molecular clusters with the metal center, avoiding aggregation during the pyrolysis process, and achieving controllable and orderly arrangement of the atoms of the metal clusters.

Benefits of technology

The controllable atomic number and uniform size of the metal cluster are achieved, the electrochemical activity and selectivity of the catalyst are improved, the Faraday efficiency of ammonia reaches 97.5%, and the current density stability is maintained for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877019A_ABST
    Figure CN119877019A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a single atom and atom accurate cluster co-loaded catalyst. According to the method, before a metal source of a metal cluster source is introduced, a stable metal molecular cluster is formed through the strong coupling effect of a 2-Methyl-1H-benzimidazole-1-methanol organic ligand and a metal center, aggregation in the subsequent pyrolysis process is effectively avoided through the strong coupling effect of the organic ligand on the metal center, so that the metal clusters are arranged in order, and the metal cluster source is formed through the strong coupling effect of the 2-Methyl-1H-benzimidazole-1-methanol organic ligand and the strong coupling effect of the 2-Methyl-1H-benzimidazole-1-methanol organic ligand. And the atom number is controllable. A series of precise atom cluster and monatomic loaded carbon carrier catalysts prepared by the method are applied to the field of electro-catalysis nitrate reduction, and efficient and oriented conversion of nitrate is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a nitrogen-doped carbon-loaded atomically precise metal cluster material (M4 / Cu-NC, where M can be a metal such as Fe, Co, Cu, etc.) and its application in the field of electrocatalysis. Specifically, the loading of different metal clusters on a single-atom carbon-nitrogen substrate produces a stronger synergistic effect at the M4 / Cu-NC catalyst interface, a method for regulating the catalytic activity of the catalyst, and its application in the field of electrocatalytic reduction of nitrate. Background Art

[0002] Electrocatalytic processes are very important in the transition from fossil fuels to renewable energy. Therefore, it is necessary to design electrocatalysts with high activity, high selectivity and high stability for specific reaction pathways under theoretical guidance. Early research focused on polycrystalline monometallic catalysts because they are simple in structure, easy to operate and convenient for research. In addition, surface-modified metals, nanoscale monometallics, bimetallics and even non-metallic materials are widely used in the field of electrocatalysis. Compared with traditional materials, nanomaterials can expose more active sites due to the size effect of smaller metal materials, thus showing different catalytic properties from traditional materials.

[0003] Similar to homogeneous catalysts, single-atom catalysts (SACs) have attracted extensive attention from researchers due to their high atomic utilization, excellent activity and selectivity for various catalytic reactions. The strong interaction between single metal atoms and the support can significantly improve the electrocatalytic performance.

[0004] Although single-atom catalysts have advantages such as clear active sites, high atomic utilization, and clear reaction mechanisms, they also face the problems of limited number of active sites and insufficient activity per unit site. Yu et al. achieved efficient electrocatalytic carbon dioxide reduction by introducing adjacent copper clusters on a copper single-atom substrate. However, since copper was directly introduced onto the carbon-nitrogen substrate during the synthesis process and then pyrolyzed, metal atoms will inevitably aggregate during the pyrolysis process, causing copper atoms to be doped on the carbon-nitrogen substrate in the form of clusters with uneven atomic numbers. Therefore, the sizes of metal clusters are uneven, which hinders further exploration of the synergistic relationship between single atoms and clusters and the reaction mechanism. [Angew.Chem.Int.Ed.2021,60,24022.]

[0005] Therefore, how to develop a method with controllable preparation and simple process to achieve precise control of metal cluster size and atomic level, precise positioning of catalyst active sites, further optimize the binding energy between active metal atoms and reaction intermediates, and achieve directional and efficient conversion of reactants is an urgent problem to be solved. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a catalyst co-loaded with single atoms and atomically precise clusters and its application in view of the deficiencies in the current technology. The method is to first form a stable metal molecular cluster with the metal center through the strong coupling effect of 2-Methyl-1H-benzimidazole-1-methanol (Hmbm) organic ligand before introducing the metal source of the metal cluster source. The strong coupling effect of the organic ligand on the metal center effectively avoids aggregation during the subsequent pyrolysis process, so that the metal cluster exists in an orderly arranged form with a controllable number of atoms. The present invention prepares a series of atomically precise clusters and single-atom loaded carbon carrier catalysts for application in the field of electrocatalytic nitrate reduction, thereby realizing efficient and directional conversion of nitrate.

[0007] The technical solution of the present invention:

[0008] A method for preparing a catalyst co-loaded with single atoms and atomically precise clusters, the method comprising the following steps:

[0009] (1) M salt, 2-Methyl-1H-benzimidazole-1-methanol (Hmbm) and triethylamine are added to anhydrous methanol to obtain a solution, which is stirred for 30 to 60 minutes and then transferred to a stainless steel Teflon reactor for hydrothermal reaction at 140 to 160° C. for 12 to 24 hours; then cooled at room temperature for 24 to 48 hours, and the product M4 molecular cluster is obtained by suction filtration;

[0010] Wherein, M salt is FeCl2·4H2O, CoCl2·6H2O or CuCl2·2H2O;

[0011] The mass ratio is Hmbm: triethylamine: M salt = 2.0-3.0: 1-1.3: 1; 150-300 mg of M salt is added to every 8 mL of anhydrous methanol;

[0012] (2) The prepared M4 molecular cluster, copper acetylacetonate and Zn(NO3)2·6H2O were then dissolved in methanol to obtain solution A, and 2-methylimidazole was then dissolved in methanol, marked as solution B; A and B were then mixed at room temperature, stirred for 1 to 1.5 hours, transferred to a reactor, and maintained at 120-140°C for 4 to 6 hours; after the solution was cooled to room temperature, the product M4 / Cu1-ZIF-8 was obtained by centrifugation and placed in a vacuum drying oven overnight.

[0013] Among them, the mass ratio of M4 molecular cluster to copper acetylacetonate is 0.95-2:1, the mass ratio of Fe4 molecular cluster to Zn(NO3)2·6H2O is 0.042-0.05:1, and the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 1.1-1.5:1.

[0014] The volume ratio of the A solution to the B solution is 2 to 3:1.

[0015] The centrifugal condition is 10000-12000rpm, maintained for 5-10min; the vacuum drying condition is 60-80℃, and the vacuum degree is 0.8-1MPa.

[0016] (3) The obtained Fe4 / Cu1-ZIF-8 is carbonized to obtain the final product Fe4 / Cu1-NC, which is a catalyst co-loaded with atomically precise metal clusters and copper single atoms.

[0017] The carbonization conditions are: maintaining at 900-1000° C. for 1-2 hours, and a heating rate of 1-8° C. / min.

[0018] The atomically precise metal clusters prepared by the method and the catalyst co-loaded with copper single atoms are used as catalytic materials for electrocatalytic reduction of nitrate.

[0019] The essential features of the present invention are:

[0020] The present invention uses the strong coupling ability of organic ligands to stabilize metal centers and form orderly arranged, uniformly sized, atomically controlled, atomically precise metal clusters. Experiments have also shown that in the subsequent pyrolysis step, the strong coupling effect of the organic ligands on the metal centers effectively avoids the inevitable aggregation during the pyrolysis process, so that the metal atoms are doped on the carbon-nitrogen substrate in the form of clusters of uniform size and controllable atomic number.

[0021] The size and atomic number of the metal clusters in the catalyst co-loaded with atomically precise metal clusters and copper single atoms prepared by the present invention are controllable, and are also extended to different metal elements (Fe, Co, Cu). The number of atoms in the clusters in the catalyst M4 / Cu-NC is precisely regulated, and aggregation does not occur during the pyrolysis process, thereby avoiding the complex and uncontrollable coordination effect between the metal and the carrier caused by high-temperature carbonization, and maintaining stability during the reaction process.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention provides a method for preparing metal clusters by stabilizing metal clusters through strong coupling between organic ligands and metal centers to form clusters with controllable atomic numbers. Compared with the conventional method of mixing metal sources with carbon-nitrogen substrates and then calcining them, the present invention effectively avoids the random arrangement of metals and the aggregation during calcination, such as Figure 1 As shown, the metal clusters of the present invention are clearly arranged in an orderly manner with four atoms, thus avoiding the phenomenon of uneven size and uncontrollable atomic number.

[0024] (2) The Fe4 / Cu1-NC obtained in the present invention exhibits excellent electrochemical activity and selectivity in the field of electrocatalytic nitrate reduction. The Faraday efficiency of conventional copper single-atom catalysts for electrocatalytic reduction of nitrate to ammonia is only 87.5%. The catalyst obtained in the present invention greatly improves the selectivity of the catalyst by introducing clusters, and the Faraday efficiency of ammonia can reach 97.5%. At the same time, it can reach the ampere level of current, which has broad industrial prospects. In addition, the single atoms and metal clusters of the catalyst obtained in the present invention are coated with a carbon shell layer. It is precisely because of the constraint effect of the carbon shell layer that the current density of the catalyst remains unchanged for 40 hours under a constant voltage. NH3 >90%, showing excellent electrocatalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a transmission electron microscope image of Fe4 / Cu1-NC prepared in Example 1.

[0026] Figure 2 This is the X-ray photoelectron spectrum of Fe4 / Cu1-NC prepared in Example 1.

[0027] Figure 3 This is a test diagram of the electrocatalytic nitrate reduction performance of the Fe4 / Cu1-NC catalyst prepared in Example 1.

[0028] Figure 4 The schematic diagram is a structural diagram of the catalyst co-loaded with copper single atoms and atomically precise metal clusters obtained in Example 1. The iron clusters can be replaced by cobalt clusters and copper clusters. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0030] The 2-Methyl-1H-benzimidazole-1-methanol (Hmbm) involved in the present invention is a known substance, specifically from Bidepharm, but not limited thereto.

[0031] Example 1

[0032] (1) Dissolve 486 mg of Hmbm and 198 mg of FeCl2·4H2O in 8 mL of anhydrous methanol. Stir for 30 min to fully dissolve, then add 197.8 mg of triethylamine and stir for another 30 min. Finally, place in a 15 mL polytetrafluoroethylene-lined reactor and perform a closed hydrothermal reaction at 140°C for 24 h. Then cool at room temperature for 24 h. Filter and wash with anhydrous methanol, and let stand to dry to obtain Fe4 molecular clusters.

[0033] (2) Dissolve 50 mg of Fe4 molecular clusters obtained in the previous step, 52 mg of copper acetylacetonate and 1.19 g of Zn(NO3)2·6H2O in 30 mL of anhydrous methanol to obtain solution A. At the same time, dissolve 1.314 g of 2-methylimidazole in 10 mL of anhydrous methanol to obtain solution B. Quickly pour solution B into solution A and stir for 1 h. Transfer it to a 150 mL polytetrafluoroethylene-lined reactor and keep it at 120°C for 4 h. After cooling to room temperature, wash it with N,N-dimethylformamide and anhydrous methanol several times, and finally place it in a vacuum drying oven at 60°C and a vacuum degree of 1 kPa overnight. Fe4 / Cu1-ZIF-8 is obtained.

[0034] (3) The obtained Fe4 / Cu1-ZIF-8 was kept at 1000°C for 1.5 h in a tube furnace at a heating rate of 5°C / min under Ar atmosphere to obtain the final catalyst Fe4 / Cu1-NC.

[0035] Example 2

[0036] The remaining steps are the same as those in Example 1, except that FeCl2·4H2O in (1) in Example 1 is replaced by CoCl2·4H2O, and the final product is Co4 molecular clusters.

[0037] (2) Dissolve 50 mg of Co4 molecular clusters obtained in the previous step, 52 mg of copper acetylacetonate and 1.19 g of Zn(NO3)2·6H2O in 30 mL of anhydrous methanol to obtain solution A. At the same time, dissolve 1.314 g of 2-methylimidazole in 10 mL of anhydrous methanol to obtain solution B. Quickly pour solution B into solution A and stir for 1 h. Transfer it to a 150 mL polytetrafluoroethylene-lined reactor and keep it at 120°C for 4 h. After cooling to room temperature, wash it with N,N-dimethylformamide and anhydrous methanol several times, and finally place it in a vacuum drying oven at 60°C and a vacuum degree of 1 kPa overnight. Obtain Co4 / Cu1-ZIF-8.

[0038] (3) The obtained Co4 / Cu1-ZIF-8 was kept at 1000°C for 1.5 h in a tube furnace at a heating rate of 5°C / min under Ar atmosphere to obtain the final catalyst Co4 / Cu1-NC.

[0039] Example 3

[0040] The FeCl2·4H2O in (1) of Example 1 is replaced by an equal amount of CuCl2·2H2O to obtain Cu4 molecular clusters.

[0041] (2) Dissolve 50 mg of Cu4 molecular clusters obtained in the previous step, 52 mg of copper acetylacetonate and 1.19 g of Zn(NO3)2·6H2O in 30 mL of anhydrous methanol to obtain solution A. At the same time, dissolve 1.314 g of 2-methylimidazole in 10 mL of anhydrous methanol to obtain solution B. Quickly pour solution B into solution A and stir for 1 h. Transfer it to a 150 mL polytetrafluoroethylene-lined reactor and keep it at 120°C for 4 h. After cooling to room temperature, wash it with N,N-dimethylformamide and anhydrous methanol several times, and finally place it in a vacuum drying oven at 60°C and a vacuum degree of 1 kPa overnight. Cu4 / Cu1-ZIF-8 is obtained.

[0042] (3) The obtained Co4 / Cu1-ZIF-8 was kept at 1000°C for 1.5 h in a tube furnace at a heating rate of 5°C / min under Ar atmosphere to obtain the final catalyst Cu4 / Cu1-NC.

[0043] Example 4

[0044] Without adding the Fe4 molecular cluster in (2) of Example 1, the remaining steps are the same as those of Example 1, and the obtained product is Cu1-NC.

[0045] Example 5

[0046] Without adding copper acetylacetonate in (2) of Example 1, the remaining steps were the same as those of Example 1, and the obtained product was Fe4-NC.

[0047] Example 6

[0048] Without adding copper acetylacetonate in (2) of Example 2, the remaining steps were the same as those of Example 2, and the obtained product was Co4-NC.

[0049] Example 7

[0050] Without adding the copper acetylacetonate in (2) of Example 3, the remaining steps were the same as those of Example 3, and the obtained product was Cu4-NC.

[0051] Figure 1 This is the transmission electron micrograph of Fe4 / Cu1-NC obtained in Example 1. It can be clearly seen from the figure that the prepared Fe4 / Cu1-NC does not undergo any agglomeration, the metal clusters are uniformly dispersed on the nitrogen-doped carbon substrate, and the average number of atoms in the clusters is 4 or 5, which belong to the close coupling of iron clusters and iron clusters of copper single atoms, respectively.

[0052] Figure 2X-ray photoelectron spectra of Fe4 / Cu1-NC, Cu1-NC and Fe4-NC prepared in Example 1, Example 4 and Example 5. It can be found from the figure that the N configuration in the catalyst is mainly pyridinic nitrogen and graphitic nitrogen, and there is an obvious metal-nitrogen bond, which illustrates the coordination of metal and nitrogen.

[0053] Figure 3 This is a performance test diagram of the electrocatalytic nitrate reduction of Fe4 / Cu1-NC prepared in Example 1. It can be seen that the catalyst with coexistence of single atoms and clusters has very excellent electrocatalytic nitrate reduction performance, high selectivity for ammonia, and the Faradaic efficiency of the generated ammonia is above 90% in a wide potential range, and can reach up to 97.5%.

[0054] Weigh 10 mg of Fe4 / Cu1-NC, add 475 μL of anhydrous ethanol, 475 μL of deionized water and 50 μL of 0.5 wt.% Nafion solution, and disperse by ultrasonic for 1 h to form a uniform dispersion. Drop 50 μL of the obtained dispersion on a carbon paper (0.25 cm 2 ) and dried naturally at room temperature.

[0055] All electrochemical tests in the present invention are carried out in a conventional three-electrode cell using a CHI760E electrochemical workstation, and the electrolyte is a mixed solution of 0.1M NaNO3 and 1M NaOH. Hg / HgO is used as a reference electrode, platinum wire is used as a counter electrode, and carbon paper coated with catalyst ink is used as a working electrode. The conversion formula between electrode potential and RHE is: E(vs.RHE)=E(vs.Hg / HgO)+0.095+0.059×pH. The test process is to conduct an electroreduction nitrate test in 0.1M NaNO3 and 1M NaOH electrolyte after Ar gas purge, and the product ammonia is detected by UV-visible colorimetry. The maximum Faraday efficiency of Fe4 / Cu1-NC in producing ammonia can reach 97.5%.

[0056] Figure 4 The schematic diagram is a structural diagram of the catalyst co-loaded with single copper atoms and atomically precise metal clusters obtained in Example 1. It can be seen from the figure that single copper atoms and metal clusters are tightly combined to form a system in which single atoms and clusters coexist.

[0057] Through experimental comparison, it was found that Fe4 / Cu1-NC has the highest Faradaic efficiency and the highest partial current density in the field of electrocatalytic reduction of nitrate, which is due to the strong hydrolysis ability of iron clusters and the strong adsorption ability of copper atoms on nitrate molecules. The electrocatalytic reduction of nitrate to ammonia is a complex eight-electron and nine-proton transfer process, in which the water at the interface of the iron cluster electrolysis catalyst provides the necessary active hydrogen for the nitrate reduction reaction, while the remaining Co4 / Cu1-NC and Cu4 / Cu1-NC have poor hydrolysis ability and competitive hydrogen evolution reaction, resulting in a decrease in the Faradaic efficiency of the ammonia product.

[0058] Example 8

[0059] The other steps are the same as those in Example 1, except that the mass ratio of Fe4 molecular clusters and copper acetylacetonate is replaced by 1.92:1 from 0.95:1, the amount of Fe4 molecular clusters added is changed from 50 mg to 100 mg, and the amount of copper acetylacetonate remains unchanged. The obtained catalyst is Fe4 / Cu1-NC*2, and the electrocatalytic nitrate reduction performance test is carried out in 0.1M NaNO3 and 1M NaOH electrolyte after Ar atmosphere purge, and the maximum Faraday efficiency is 60.02%.

[0060] Example 9

[0061] The other steps are the same as those in Example 1, except that the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 1.1 :1 was replaced with 1.5~1, and the obtained catalyst was Fe4 / Cu1-NC-Zn*1.5. The electrocatalytic nitrate reduction performance test was carried out in 0.1M NaNO3 and 1M NaOH electrolyte after Ar atmosphere purging, and the maximum Faraday efficiency was 43.02%.

[0062] Example 10

[0063] The other steps are the same as those in Example 1, except that the centrifugal speed in step (2) in Example 1 is replaced by 10 min from 5 min, and the obtained catalyst is Fe4 / Cu1-NC-rpm12000. The electrocatalytic nitrate reduction performance test is carried out in 0.1M NaNO3 and 1M NaOH electrolyte after Ar atmosphere purge, and the maximum Faraday efficiency is 67.98%.

[0064] Embodiment 11

[0065] The other steps are the same as those in Example 1, except that the calcination temperature in step (3) in Example 1 is replaced by 900°C from 1000°C, and the obtained catalyst is Fe4 / Cu1-NC-900°C. The electrocatalytic nitrate reduction performance test is carried out in 0.1M NaNO3 and 1M NaOH electrolyte after Ar atmosphere purge, and the maximum Faraday efficiency is 87.06%.

[0066] The obtained material properties show that the highest Faradaic efficiency of Fe4 / Cu1-NC electrocatalytic nitrate reduction is 97.5% at -0.38 V vs. RHE, and the partial current density of ammonia product is 86.05 mA cm -2 , which has good prospects for industrial application. In contrast, the Faradaic efficiency of Cu1-NC is only 74.9%, and the partial current density of ammonia is 26.92 mA cm -2 The Faradaic efficiency of Fe4-NC is 75.2%, and the partial current density of ammonia is 22.38 mA cm -2 After replacing the clusters with Co4 molecular clusters and Cu4 molecular clusters, the Faradaic efficiency of Co4 / Cu1-NC was 54.13%, and the partial current density of ammonia was 4.83 mA cm -2 The Faradaic efficiency of Cu4 / Cu1-NC is 79.49%, and the partial current density of ammonia is 60.75 mA·cm -2 .

[0067] It can be seen from the above examples that the M4 / Cu1-NC prepared in the present invention forms well-arranged metal clusters on the nitrogen-doped carbon substrate through the strong coupling effect of the organic ligands, and different properties of the metal clusters lead to different performances of electrocatalytic nitrate reduction.

[0068] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a catalyst co-loaded with single atoms and atomically precise clusters, characterized in that the method comprises the following steps: (1) M salt, 2-Methyl-1H-benzimidazole-1-methanol, and triethylamine are added to anhydrous methanol to obtain a solution, which is stirred for 30 to 60 minutes, and then transferred to a reaction kettle and maintained at 140 to 160° C. for 12 to 24 hours; then cooled at room temperature for 24 to 48 hours, and the product M4 molecular cluster is obtained by suction filtration; in, M salt is FeCl2·4H2O, CoCl2·6H2O or CuCl2·2H2O; The mass ratio is Hmbm: triethylamine: M salt = 2.0-3.0: 1-1.3: 1; 150-300 mg of M salt is added to every 8 mL of anhydrous methanol; (2) Then, the prepared M4 molecular cluster, copper acetylacetonate and Zn(NO3)2·6H2O were dissolved in methanol to obtain solution A, and then 2-methylimidazole was dissolved in methanol, which was marked as solution B; then, A and B were mixed at room temperature, stirred for 1 to 1.5 hours, transferred to a reactor, and kept at 120-140°C for 4 to 6 hours; after the solution was cooled to room temperature, it was centrifuged and vacuum dried to obtain the product M4 / Cu1-ZIF-8; The mass ratio of the M4 molecular cluster to copper acetylacetonate is 1 to 2:1, the mass ratio of the Fe4 molecular cluster to Zn(NO3)2·6H2O is 0.042 to 0.05:1, and the mass ratio of the 2-methylimidazole to Zn(NO3)2·6H2O is 1.1 to 1.5:1; (3) The obtained Fe4 / Cu1-ZIF-8 is carbonized to obtain a catalyst in which atomically precise metal clusters and copper single atoms are co-loaded.

2. The method for preparing a catalyst co-loaded with single atoms and atomically precise clusters as claimed in claim 1, characterized in that: The centrifugal condition in step (2) is 10000-12000 rpm, maintained for 5-10 min; the vacuum drying condition is 60-80° C., and the vacuum degree is 0.8-1 MPa.

3. The method for preparing a catalyst co-loaded with single atoms and atomically precise clusters as claimed in claim 1, characterized in that: The volume ratio of solution A to solution B is 2-3:

1.

4. The method for preparing a catalyst co-loaded with single atoms and atomically precise clusters as claimed in claim 1, characterized in that: The carbonization conditions are: maintaining at 900-1000° C. for 1-2 hours, and a heating rate of 1-8° C. / min.

5. Use of a catalyst co-loaded with atomically precise metal clusters and copper single atoms prepared by the method of claim 1, characterized in that: As a catalytic material for the electrocatalytic reduction of nitrate.

Citation Information

Patent Citations

  • Method for synthesizing micro / nano zeolitic imidazolate frameworks (ZIFs)

    CN102335626A

  • Mixed ligand zeolitic imidazole framework, preparation method and application to carbon dioxide selective adsorption

    CN103951684A

  • Two-dimensional material supported monatomic doped Au24M bimetallic cluster electrocatalyst

    CN113782756A

  • Stable and efficient synergistic catalyst with general formula of M+MxPy / PBNC as well as preparation method and application thereof

    CN117160506A

Cited By

  • Solar thermal field-electrocatalysis synergistic copper-based catalytic material for groundwater pollution remediation, preparation method, water treatment device and application

    CN121513939A